SUICIDAL IDEATION BY INCARCERATED INMATES OF KUJE MEDIUM CUSTODIAL CENTRE ABUJA: PERSONALITY TRAITS, SELF-BLAME AND PERCEIVED SOCIAL SUPPORT AS FACTORS - Gerald, Chidera Ijeoma; Atafo, Dennis O.; Ruwan, Felix I.I. (African Journal of Social and Behavioural Sciences, 2024)
The psychological effect of being incarcerated takes a toll on inmates, which is often characterized by withdrawal, despair, melancholy and deprivation, and a combination of these effects plays a significant role on inmates. As such, inmates are more likely to contemplate suicide or be prone to suicide. Therefore, this study explores personality traits, self-blame and perceived social support as predictive factors of suicidal ideation among incarcerated inmates of the Kuje Medium Security Custodial Centre, Abuja. The study instruments were completed by providing informed consent. The suicidal ideation scale (SIS), The Big Five Personality Inventory scale (BFI), the Self-blame Sub-scale (SBSS) of Cognitive Emotion Regulation Questionnaire (CEMRQ) and Multidimensional Scale of Perceived Social Support (MSPSS) scores were collected and analysed using SPSS version 27. The result revealed that personality traits (extraversion, agreeableness, conscientiousness, neuroticism and openness to experience) jointly predicted suicidal ideation (R= .857, F= 78.863, P < .01). Findings also revealed that self-blame had no significant influence on suicidal ideation (R= .122; F= 2.216, P > .05). In addition, the result revealed that social support had a significant influence on suicidal ideation (R= .893; F= 573.575 P < .01). Overall, personality traits, self-blame and perceived social support jointly and significantly predicted suicidal ideation (R= .388; F= 15.507, P < .01) among incarcerated inmates. It was recommended that Kuje Medium Security Custodial Centre, Abuja should endeavour to engage inmates in therapeutic programmes and clinical interventions that will help them to gain self-awareness and enhance their psycho-emotional development.